In a Vision of the Night : Job, Cormac McCarthy, and the Challenge of Chaos - Thomas, Philip S. (Philip Strephon), 1973- (Book collections on Project MUSE., 2021)
"Employs a thematic reading of Cormac McCarthy's works to explore themes of creation, chaos, purpose, and theodicy in the book of Job"--